English Language Learning Anxiety and its Relationship with Language Achievement: A Study on Learners in a Technical University - Balakrishnan, Subatira; Abdullah, Nurlisa Loke; Linda Khoo, Mei Sui (Journal of Technical Education and Training, 2020)
Learning English has never been easy in an environment where it is seldom used. As such there is possibility that English language learners may suffer from language learning anxiety which could affect their language achievements.The present study aim is to examine the level of English language learning anxiety experienced by Diploma students in Universiti Tekinikal Malaysia Melaka (UTeM). It also intends to determine if there is a relationship between the level of anxiety in the English language learning and the students’ English language achievements in the national examination. Additionally, the study intends to identify if there is a difference in the level of English language learning anxiety between genders among the Diploma students in UTeM. Based on this, a sample of 125 students of first semester Diploma in Information Technology (DIT) were given a set of Foreign Language Classroom Anxiety Scale (FLCAS) survey forms which was adapted from the original FLCAS version (Horwitz, et al., 1986). The students’ English language grades at SPM level were used as the measurement of their English language achievement. The findings revealed that the students experienced a moderate level of English language learning anxiety (M= 2.68). The results of Pearson correlation showed there is a significant negative relationship between total FLCA scores and SPM English language achievement scores (r = -.360, n = 125, p < 0.05). It was also discovered that the male diploma students experienced a higher level of English language learning anxiety (M=2.758) compared to the female students (M=2.593) of their cohort. In conclusion, the present study suggests that language educators need to provide positive experiences and conducive environment for English language learners. This is because unthreatening English lessons will definitely help TVET and MTUN undergraduates enhance their English communication skills.